The Danger of Drugs for Adolescent Development in the Perspective of Law No. 35 of 2009 - Samsuria Samsuria (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
The latent danger of drugs is a big enemy for all humanity, and this is because the impact resulting from their misuse has a fatal effect on anyone who uses them. Today's drug circulation has penetrated among teenagers as a vital part of the nation's generation, the tendency of the dangers of drugs to development among teenagers certainly has a lot of effects on the situation and conditions of the social climate among the community, considering the most urgent thing when discussing adolescent development is how the substance of the younger generation a nation that the dangers of drug abuse have invaded. The enactment of Law Number 35 of 2009 certainly brings fresh air for law enforcement elements in Indonesia, but not for those addicted to drug abuse. The method used in this research is a normative juridical approach, namely by conducting research based on legal/reference materials by examining the theories and concepts of these legal materials, which are related to the legal principles of statutory regulations, invitations associated with this writing/research.